Anesthesia with Propofol versus Sevoflurane: Does the Longer Neuromuscular Block under Sevoflurane Anesthesia Reduce Laryngeal Injuries?. (27th February 2013) - Mencke, Thomas; Zitzmann, Amelie; Machmueller, Susann; Boettcher, Arne; Sauer, Martin; Pau, Hans-Wilhelm; Noeldge-Schomburg, Gabriele; Dommerich, Steffen
Abstract : Anesthesia can be maintained with propofol or sevoflurane. Volatile anesthetics increase neuromuscular block of muscle relaxants. We tested the hypothesis, that sevoflurane would cause less vocal cord injuries than an intravenous anesthesia with propofol. In this prospective trial, 65 patients were randomized in 2 groups: SEVO group, anesthesia with sevoflurane, and TIVA group, total intravenous anesthesia with propofol. Intubating and extubating conditions were evaluated. Vocal cord injuries were examined by stroboscopy before and 24 and 72 h after surgery; hoarseness and sore throat were assessed up to 72 h after surgery. Hoarseness and sore throat were comparable between both groups (not significant). Similar findings were observed for vocal cord injuries: 9 (SEVO) versus 5 (TIVA) patients;P = 0.36 ; the overall incidence was 24%. Type of vocal cord injuries: 9 erythema and 5 edema of the vocal folds. Neuromuscular block was significantly longer in the SEVO group compared with the TIVA group: 71 (range: 38–148) min versus 52 (range: 21–74) min;P < 0.001 . Five patients (TIVA group) versus 11 patients (SEVO group) needed neostigmine to achieve a TOF ratio of 1.0( P = 0.14 ) . Under anesthesia with propofol laryngeal injuries were not increased; the risk for residual curarization, however, was lower compared with sevoflurane.